2022
DOI: 10.1055/s-0041-1736297
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Premature Ovulation by Administration of Gonadotropin Releasing Hormone Antagonist the day After Ovulation Triggering in Diminished Ovarian Reserve Patients

Abstract: Objective The aim of the present retrospective study was to investigate the effectiveness of single-dose gonadotropin releasing hormone (GnRH) antagonist administration, the day after human chorionic gonadotropin (hCG) triggering for final oocyte maturation, on the prevention of premature luteinization in patients with diminished ovarian reserve in in-vitro fertilization (IVF) cycles. The secondary objective of the study was to search the effect of this protocol on pregnancy outcomes. Methods This is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
(31 reference statements)
0
1
0
Order By: Relevance
“…From stimulation day 6 onwards, women's gonadotropin doses were adjusted according to serum E2 levels and ovarian response, which was assessed through vaginal ultrasonography every 2 days. For patients treated with E2 (n=50), doses of E2 valerate were started on day 20 of the menstrual cycle prior to the IVF/ICSI cycle at a daily dose of 4 mg (2 mg twice daily) orally for 5 to 12 days, until the day before the start of ovarian stimulation, regardless of the specific day of the onset of menstruation [12]. No significant differences were observed in the number of oocytes retrieved, fertilization rates, number of top-quality embryos or number of transferred embryos [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From stimulation day 6 onwards, women's gonadotropin doses were adjusted according to serum E2 levels and ovarian response, which was assessed through vaginal ultrasonography every 2 days. For patients treated with E2 (n=50), doses of E2 valerate were started on day 20 of the menstrual cycle prior to the IVF/ICSI cycle at a daily dose of 4 mg (2 mg twice daily) orally for 5 to 12 days, until the day before the start of ovarian stimulation, regardless of the specific day of the onset of menstruation [12]. No significant differences were observed in the number of oocytes retrieved, fertilization rates, number of top-quality embryos or number of transferred embryos [13].…”
Section: Discussionmentioning
confidence: 99%
“…Using research databases, information is identified, selected, analyzed, and synthesized. The knowledge imparted by the general conclusion of the study enables enhancement of patient care and improvement in the professional routine [12].…”
Section: Methodsmentioning
confidence: 99%
“…(7,12,14) The GnRH pulse in women with PCOS shows a predominance of LH synthesis, which stimulates the theca cells to convert cholesterol into androstenedione, one of the androgenic hormones. (12,15,16) As a result, the body enters a stage of hyperandrogenism. Furthermore, FSH will be released in less quantity by the pituitary gland, and the ovary, in turn, will not produce estrogen properly.…”
Section: Polycystic Ovary Syndromementioning
confidence: 99%
“…In patients with POR, LH spontaneous surges often appear as hidden peaks; therefore, it is difficult to control spontaneous premature ovulation, which is also one of the main reasons for the high cancellation rate. Gonadotropin-releasing hormone antagonist (GnRH-ant) can rapidly inhibit LH secretion [ 18 ], thus preventing premature luteinization and ovulation in COS [ 19 , 20 ]. Some studies showed that GnRH-ant may affect follicle growth and endometrial receptivity [ 21 ].…”
Section: Introductionmentioning
confidence: 99%